Pengembangan LKPD Berbasis Project Based Learning pada Materi Kekayaan Budaya Indonesia di Kelas IV SD 39 Pontianak Kota : Penelitian - Sri Yulia Ningsih; Kartono; Rio Pranata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to develop a Project-Based Learning (PjBL) Student Worksheet (LKPD) for the Natural and Social Sciences (IPAS) subject on the theme of Indonesian Cultural Wealth for fourth-grade students at SDN 39 Pontianak Kota. The research used a Research and Development (R&D) method with a mixed-method approach that combined quantitative and qualitative data. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed because of its systematic and flexible structure. The LKPD was designed to integrate PjBL stages explicitly, apply communicative language suitable for students’ developmental levels, and feature attractive, contextual visuals. Expert validation in design, language, and content showed high feasibility, with scores of 87.5%, 97.5%, and 81.67%. Student responses were also very positive, reaching 98.57% in the small group trial and 88.52% in the large group trial. Overall, the findings confirmed that the PjBL-based LKPD was feasible and effective as a learning tool, increasing student engagement and motivation while fostering collaboration, communication, and critical thinking as essential 21st-century skills.